The effect of Physical Education teachers' autonomy support on college students' basic psychological needs and physical exercise - Wenjuan Zhang; Chairat Choosakul (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: This study applied self-determination theory to investigate the mediating effect of basic psychological needs between exercise autonomy support and exercise behavior, to construct a path model for promoting college students' participation in physical exercise, and to provide a theoretical basis for intervention of college students' physical exercise behavior.